PENEGAKAN HUKUM TINDAK PIDANA DALAM PASAL 310 UNDANG-UNDANG NOMOR 22 TAHUN 2009 OLEH PENYIDIK SATUAN LALU LINTAS POLRES KUTAI TIMUR - Ahmad Abu Bakar (Universitas 17 Agustus 1945 Samarinda, 2020)
AbstractTraffic violations are a problem that often occurs on the highway. In cases of traffic violations, in general there is no element of intent, only the element of neglect. Due to his negligence or negligence, the actions of the traffic violation perpetrator can cause the victim to fall and can cause death to the victim Almost all accidents due to human factors are preceded by violations of traffic signs or regulations. The legal consequences due to the negligence of a person who commits a traffic violation causing an accident are clearly regulated in Article 310 of Law Number 22 of 2009. The process of investigating criminal acts of Article 310 of Law Number 22 of 2009 by Traffic Unit Investigators of the East Kutai Police, namely: (1) notifying units in the field to pursue, intercept and arrest, (2) search and collect information from victims and/or witnesses, (3) research the evidence at the TKP, (4) identify types of accidents traffic, (5) shooting crime scenes and evidence, (6) informing the Control Center for the Information and Communication System for Traffic and Road Transportation and operational units, (7) inspections at places thought to be used to change the identity of the vehicle and/or hiding the vehicle if the perpetrator runs away; (8) blocking Motorized STNK, and (9); submission of evidence to the forensic laboratory. Obstacles in the law enforcement process against Article 310 of Law Number 22 Year 2009 by the East Kutai Police Traffic Unit investigators, from: (1) internal factors, the limited number of Polri personnel, and the number of unsupportive facilities, and (2) external factors is the difficulty in determining and calling witnesses for questioning. Keywords: Crime, Investigators,Law Enforcement, Traffic